Consecutive Eyeball Pressure Tests Reflect Clinically Relevant Vagal Dysfunction and Recovery in a Patient With Guillain-Barré-Syndrome With Tenacious Cardiac Dysautonomia - Anouck Becker; Stefanie Behnke; Silke Walter; Silke Walter; Mathias Fousse; Axel Buob; Jan Bürmann; Klaus Faßbender; Marcus M. Unger (Frontiers in Neurology, 2020)
Cardiac dysautonomia is a potentially life-threatening complication of Guillain-Barré syndrome (GBS). Proper and prompt recognition of patients at risk and subsequent intensive care unit (ICU) monitoring are mandatory to prevent fatal outcome. Eyeball pressure testing (EP) has been suggested as an easy applicable bedside test for vagal overreactivity in GBS and thus identifying patients at risk. Yet, there is only sparse follow-up data concerning the course of EP findings in GBS. We report a 25 years-old male patient with GBS who underwent consecutive EP (n = 11) during his ICU stay over a period of 11 weeks. The series of tests performed in this patient (and corresponding clinical events) show that EP data might represent an approximation of vagal dysfunction and vagal recovery in GBS. Interestingly, we observed a much longer duration of pathological EP compared to a previous report. The tenacious cardiac dysautonomia in this patient necessitated long-term application of a transvenous temporary pacemaker.